Microbial communities in the phyllosphere and endosphere of Norway spruce under attack by Heterobasidion - Meng, Wen-jing; Wen, Zi-lan; Kasanen, Risto; Sun, Hui; Asiegbu, Fred O. (Frontiers in Microbiology, 2025)
Heterobasidion annosum species complex has been regarded as the most destructive disease agent of conifer trees in boreal forests. Tree microbiome can regulate the plant–pathogen interactions by influencing both host resistance and pathogen virulence. Such information would help to improve the future health of forests and explore strategies to enhance ecosystem stability. In this study, using next-generation sequencing technology, we investigated the microbial community in different tree regions (needles, upper stem, and lower stem) of Norway spruce with and without wood decay symptoms. The primary purpose was to uncover signature characteristic microbiome harbored by asymptomatic trees compared to diseased trees. Additionally, the study was to explore the inter-kingdom and intra-kingdom interactions in microbiome (bacteria and fungi) of symptomatic versus asymptomatic trees. The results showed that in upper stem, species richness (Chao1) of fungi and bacteria were both higher in asymptomatic trees than symptomatic trees (P < 0.05). Compared to symptomatic trees, asymptomatic trees harbored a higher abundance of Actinobacteriota, bacterial genera of Methylocella, Conexibacter, Jatrophihabitans, and fungal genera of Mollisia. Fungal communities from the same anatomic region differed between the symptomatic and asymptomatic trees. Bacterial communities from the two stem regions were also distinct between the symptomatic and asymptomatic trees. The symptomatic trees possessed a less stable microbial network with more positive correlations compared to the asymptomatic trees. In the lower stem, at intra-kingdom level, the distribution of correlation numbers was more even in the bacterial network compared to the fungal network. In conclusion, the Heterobasidion attack decreased the microbial community species richness and shifted the community structure and functional structure to varying degrees. The microbial network was enlarged and became more unstable at both inter-kingdom and intra-kingdom level due to the Heterobasidion infection.